Cell association in rous sarcoma virus (RSV) rescue and cell infection - Svoboda, Jan (Folia biologica (Praha), 2015)
In my article I tried to present the results of early experiments suggesting a significant role for cell association in Rous sarcoma virus transformation of non-permissive cells and revealing that infectious virus can be efficiently rescued from such cells by their fusion with permissive chicken fibroblasts.
Keywords: Virus Replication; ptačí sarkom; Rous sarcoma virus; kur domácí; Animals; Cell Transformation, Viral; Chickens; proviry; virová transformace buněk; Proviruses; krysa rodu Rattus; zvířata; replikace viru; virus Rousova sarkomu; Sarcoma, Avian; Rats